TANTANGAN PENGIMPLEMENTASIAN LAPORAN KEUANGAN SESUAI SAK-EMKM PADA UMKM BATIK JETIS SIDOARJO - Handayani, Astrid Tri Safira; Salsabila, Shofiyah Nugraha; Hanifah, Fitrotunnisa Nur; Azzahru, Dewi; Prastiwi, Niken; Lating, Ade Irma Suryani; Aristantia, Selvia Eka; Muflihin, Mohammad Dliyaul; Yudhanti, Ashari Lintang; Junjunan, Mochammad Ilyas (Jurnal AbdiMas Nusa Mandiri, 2026)
The community service in Batik Jetis Sidoarjo MSMEs aims to provide an understanding to business actors about the importance of implementing the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). In addition, this activity also includes assistance for MSME players in implementing SAK EMKM, which plays an important role in improving the quality of their financial statements. The problem faced by craftsmen in Kampung Jetis is the lack of ability and knowledge of business actors related to the implementation of effective accounting. Therefore, this assistance is expected to help them understand and apply accounting better to support the sustainability of their business. This service method is carried out in 3 stages, including: Observation, Socialization, and Assistance. The results of observations and interviews show that the majority of MSME actors do not understand standardized financial records and still use simple bookkeeping. Socialization was carried out through basic accounting training, followed by pretest and posttest to measure the increase in understanding. Furthermore, mentoring was provided to two MSME players, namely Bu Ratna and Pak Rinaldi, with a focus on digitizing financial records and separating business and personal assets. The results of this program show that intensive education and mentoring are necessary for MSMEs to effectively implement SAK-EMKM.